¿Quo Vadis Public Health? Discourse and Practice of Public Health in Peru, and its Universitary Apogee in the 1990's - Murillo Peña, Juan (2000)
In Peru since mid 1990s it has there been a rapid increase in the offering of Postgraduate Programmes in Public Health and related fie1ds. Taking into aecount that a significant number of professionals has graduated from these programmes, it is mandatory to state the question of whether can we talk about an intellectual collectivity in this knowledge field or cannot. The analysis of the components that integrate an intellectual collectivity shows that in the academical field of our country, Public Health expresses a peculiar way of pre-modem assimilation of the positivist discourse. Therefore, public health has never been assimilated into a practice and an institutional collective memory that allow it to set up as a modern discourse. The stage of the last decade confiriris that the core of the problem ís of cultural nature. The premodern culture of our academical institutions makes that the postgraduate programmes do not contribute to the necessary generation of a collectivity that allows a relevant development of the peruvian Public health.